2018
DOI: 10.1155/2018/3270293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multilaminate Small Intestinal Submucosa as a Barrier Membrane on Bone Formation in a Rabbit Mandible Defect Model

Abstract: A barrier membrane (BM) is essential for guided bone regeneration (GBR) procedures. Absorbable BMs based on collagen have been widely applied clinically due to their excellent biocompatibility. The extracellular matrix (ECM) provides certain advantages that can compensate for the rapid degradation and insufficient mechanical strength of pure collagen membrane due to the porous scaffold structure. Recently, small intestinal submucosa (SIS), one of the most widely used ECM materials, has drawn much attention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In a rat cranial defect model, significant new bone formation can be observed in defect areas covered by the SIS membrane, particularly in areas close to the membrane [16]. Similar results have been achieved using mSIS combined with the bone substitute material in mandibular bone defects in a rabbit model [17]. Here, we compared the mSIS membrane with widely used collagen membranes for GBR in beagle implant models utilizing clinical methods.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In a rat cranial defect model, significant new bone formation can be observed in defect areas covered by the SIS membrane, particularly in areas close to the membrane [16]. Similar results have been achieved using mSIS combined with the bone substitute material in mandibular bone defects in a rabbit model [17]. Here, we compared the mSIS membrane with widely used collagen membranes for GBR in beagle implant models utilizing clinical methods.…”
Section: Discussionsupporting
confidence: 59%
“…e mSIS comprised eight layers of acellular monolayer porcine SIS, produced as a lyophilized stack. e manufacturing process is described in a previous paper [17].…”
Section: Preparation Of Msismentioning
confidence: 99%
See 1 more Smart Citation
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%
“…The large values of Tb.Th and Tb.N indicate the maturity and stability of the bone structure. By contrast, if the value of Tb.Sp, which represents the degree of connectivity of the trabecular bone, is large, the arrangement of the bone structure is poor 23) . It was found that the Tb.N and Tb.Th of the three groups were higher than those of the control group from Table 2 at postoperative weeks 4 and 12.…”
Section: Micro-ct Analysismentioning
confidence: 99%